Respons Pertumbuhan Tembakau Deli (Nicotiana tabacum L.) Terhadap Pemberian Pupuk Nitrogen dan Zeolit - Dedek Irawan; Irsal Irsal; Haryati Haryati (Universitas Sumatera Utara, 2015)
This research has been conducted to study the effect of nitrogen fertilizer and zeolite on growth of tobacco. This research has been conducted in screen house at the Faculty of Agriculture, University of Sumatera Utara, Medan (± 25 m above sea level) during September until November 2014 using factorial randomized block design with two factors are nitrogen fertilizer (0; 9,02; 18,04 g ZA/plant) and zeolite ( 0; 31,5; 63,1; 94,6 g/plant). The parameters observed were plant height, diameter of stem, numbers of leaf, greennes of leaf and summarize of leaf area. The results of the research showed that nitrogen fertilizers increased plant growth of tobacco Deli, zeolites and both of interaction has not increase plant growth of tobacco Deli.Key words : nitrogen, zeolite, Deli tobacco.